“Lessons from things” in the Museum: The intuitive method and the State Museum of Rio Grande do Sul in the first decades of the 20th century. - Possamai, Zita Rosane (Education Policy Analysis Archives, 2012)
The republican regime in Brazil was established amid deep transformation that made demands for social modernization. Within this context, education and schooling were considered very important for the creation of citizenship aligned with new ideas to produce a scientific society. For that reason, it was vital to look for new teaching methods that followed the precepts of a pedagogic modernity. Here enters the valorization of the intuitive method or “lessons from things”, based on the observation and the experience (the concrete), while the traditional teaching method was criticized as based on memorization, repetition and abstraction. In Brazil and especially in Rio Grande do Sul, that method was adopted by the state government and incorporated within the teaching system. The State Museum of Rio Grande do Sul was created within the same republican context. It gave especial attention to the creation of natural science collections. In that period, the school considered this museum as a useful laboratory to put the intuitive method in practice and therefore the museum supplied the school with the necessary material for the “lessons from things” teaching.